A reappraisal of Mesozoic-Cenozoic sequence stratigraphy in Offshore Indus Basin, Pakistan (Kuwait Journal of Science)
The Offshore Indus Basin is a passive continental margin and a frontier zone for hydrocarbon exploration based on structural and stratigraphic features observed on seismic data. In this study, the seismic and biostratigraphic framework is established using seismic data, geophysical well logs, along with biostratigraphic information to define the depositional sequences in the study region. A re-examination of the seismic data exhibits normal faults and a total of six seismic sequences ranging from Cretaceous to Quaternary. Nummulites atacicus, Nummulites globulus, Discocyclina sp., Miscellanea miscella, and Ranikothalia sp. are the major identified fauna in the Karachi South A1 well (2030–2724 m). The Miscellanea miscella, Ranikothalia, and Discocyclina sp. ages range from 55 to 56.5, 55–59, and 55–59 Ma respectively. Employing biostratigraphy, Ranikothalia/Miscellanea miscella/Discocyclina biozone (55–59 Ma), a single sequence, a third order cycle of deposition and transgressive and highstand system tracts have been recognized in the Karachi South A1 well. Linking biostratigraphic results to seismic stratigraphy indicates that the strata located in the range of 2030–2724 m is of the Ranikot (Paleocene) Formation and has been previously given Eocene age rather than the Paleocene using vintage seismic data. The environment of deposition of the Ranikot Formation in the Karachi South A1 well is the subtidal environment of the middle-shelf (30–45m depth) setting. © 2024